2018
DOI: 10.1038/s41467-018-06297-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced voltage generation through electrolyte flow on liquid-filled surfaces

Abstract: The generation of electrical voltage through the flow of an electrolyte over a charged surface may be used for energy transduction. Here, we show that enhanced electrical potential differences (i.e., streaming potential) may be obtained through the flow of salt water on liquid-filled surfaces that are infiltrated with a lower dielectric constant liquid, such as oil, to harness electrolyte slip and associated surface charge. A record-high figure of merit, in terms of the voltage generated per unit applied press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 43 publications
0
71
1
Order By: Relevance
“…In recent years, energy harvesting devices that utilize water as an energy source have gained great attention since water is the most abundant and ubiquitous liquid on earth. [1][2][3] A variety of devices have been reported, where each device requires their own methods for water supplementation. [1][2][3][4][5][6] For example, Liang, et al demonstrated a graphene oxide (GO) paper-based moisture-driven electric power generator, 5 and Xu et al presented a pristine GO film-based water diffusion-driven power generator.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, energy harvesting devices that utilize water as an energy source have gained great attention since water is the most abundant and ubiquitous liquid on earth. [1][2][3] A variety of devices have been reported, where each device requires their own methods for water supplementation. [1][2][3][4][5][6] For example, Liang, et al demonstrated a graphene oxide (GO) paper-based moisture-driven electric power generator, 5 and Xu et al presented a pristine GO film-based water diffusion-driven power generator.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid‐lined porous structures of lungs provide mechanical compliance for breathing and facilitate selective transportation of gas. Inspired from these natural liquid‐lined structures, various liquid‐infused channels and materials have been fabricated for applications in medical, environmental, and energy‐related fields . Liquids are mobile and have random shapes in bulk systems, while they can be fixed in micro‐/nanoscale channels due to the capillary force, and the van der Waals force between the solid surface and fluids.…”
Section: Inner Surface Design Of Microchannelsmentioning
confidence: 99%
“…Above experimental results indicated the importance of the chemistry matching between the microchannel surfaces and functional liquid, and the surface roughness for building of liquid‐infused microchannels. Bandaru and co‐workers reported the electrolyte flow in the liquid‐filled microchannels for the study of electrokinetic phenomena at the microscale (Figure B) . The liquid‐filled microchannels were prepared through bonding straight‐line patterned PDMS microchannels with liquid‐filled grooves patterned silicon surfaces.…”
Section: Inner Surface Design Of Microchannelsmentioning
confidence: 99%
See 2 more Smart Citations